Minat Pelaku Usaha Pengolahan Ikan Terhadap Pemanfaatan Teknologi Digital Marketing - Imadudin, Rifki Muhamad; Djuliansah, Dedi; Mutolib, Abdul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Digital marketing is a marketing strategy that utilises technology and digital platforms to reach, interact and build relationships with customers that can be accessed by businesses. But there are still many fish processors who are members of the fish processing and marketing group who have not done digital marketing. This study aims to analyse the interest of business actors in digital marketing technology, and analyse the effect of business actors' interest in the factors that influence interest in digital marketing technology. This research was conducted in Tasikmalaya City in October 2024 - April 2025 to fish processing business actors who are members of fish processing and marketing groups with a sample of 35 people. For the analysis method used, namely quantitative descriptive analysis and multiple linear regression analysis. The results showed that the interest of fish processing businesses in digital marketing technology was in the high category. Jointly, variables including age, education, income, business scale, experience, knowledge, convenience, trust, usefulness, profit, risk perception, and access to technology have a significant influence on the interest of fish processing businesses in digital marketing technology. The variables of education, income, business scale, and access to technology each have a strong influence on the interest of fish processors in digital marketing technology.